MDM2 is involved in the regulation of p53 expression in the immune response of oyster Crassostrea hongkongensis. (March 2022) - Zhang, Aijiao; Yang, Yucheng; Zeng, Liang; Zhao, Zehui; Zhou, Yinyin; Yang, Zhuo; Liao, Qingliang; Xiao, Shu; Ma, Haitao; Li, Jun; Mao, Fan; Qin, Yanping; et al.
Abstract: MDM2 (mouse double-minute) and p53 form a negative feedback loop and play a prominent role in preventing the induction of uncontrolled apoptosis. To better understand their potential roles in oyster Crassostrea hongkongensis, MDM2 and p53 homologs were first isolated and cloned in C. hongkongensis (named Ch MDM2 and Ch p53), and their mRNA expression patterns in tissues and developmental stages were analyzed. Multiple sequence alignment analysis and phylogenetic analysis of Ch MDM2 and Ch p53 displayed a high degree of homology and conservation. In addition, exposure to Vibrio coralliilyticus resulted in DNA damage and apoptosis in the hemocytes of C. hongkongensis, and found that the mRNA expression level of Ch MDM2 was decreased, while the relative expression of Ch p53 was significantly increased in the hemocytes and gills. Furthermore, fluorescence from Ch MDM2-EGFP and Ch p53-Red were found to be distributed in the nucleus of HEK293T cells. Besides, dual-luciferase reporter assays showed that Ch MDM2 antagonized with Ch p53 and participates in p53 signaling pathway. In addition, the interaction between Ch MDM2 and Ch p53 was confirmed strongly by Co-immunoprecipitation assays. Furthermore, the results of RNAi showed that Ch MDM2 and Ch p53 participated in apoptosis which induced infection of V. coralliilyticus . Taken together, our results characterized the features of Ch MDM2 and Ch p53, which played a critical role in apoptosis of C. hongkongensis . Highlights: Ch MDM2 and Ch p53 were first isolated and cloned from C. hongkongensis. Ch MDM2 antagonized with Ch p53 and participates in p53 signaling pathway. Ch MDM2 and Ch p53 were located in the nucleus of HEK293T cells. Ch MDM2 and Ch p53 participated in apoptosis during V. coralliilyticus infection.